2003
DOI: 10.4049/jimmunol.171.2.608
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Activates Both Innate and Adaptive Immunity to Generate Potent Antitumor Responses that Require Perforin but Are Independent of IFN-γ

Abstract: IL-21 is a key factor in the transition between innate and adaptive immune responses. We have used the cytokine gene therapy approach to study the antitumor responses mediated by IL-21 in the B16F1 melanoma and MethA fibrosarcoma tumor models in mice. Retrovirally transduced tumor cells secreting biologically functional IL-21 have growth patterns in vitro similar to that of control green fluorescent protein-transduced cells, but are completely rejected in vivo. We show that IL-21 activates NK and CD8+ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 50 publications
7
150
0
1
Order By: Relevance
“…Our work demonstrating the concurrent production of high levels of granzyme B by nearly all cells of a highly cytolytic effector population that is uniformly unable to produce IFN-␥, provides the strongest evidence to date for the uncoupling of cytotoxicity and IFN-␥ secretion within a single CD8 T cell. Consistent with the results described here, Ma et al (21) have described clearance of an IL-21-secreting tumor by a CD8-and NK cell-dependent mechanism requiring perforin but not IFN-␥. Furthermore, we have observed an E.G7 tumor-infiltrating, Ag-specific population of granzyme B high, IFN-␥ negative CD8 effector cells (J. M. Curtsinger, M. Y. Gerner, D. C. Lins, and M. F. Mescher, unpublished data).…”
Section: Discussionsupporting
confidence: 80%
“…Our work demonstrating the concurrent production of high levels of granzyme B by nearly all cells of a highly cytolytic effector population that is uniformly unable to produce IFN-␥, provides the strongest evidence to date for the uncoupling of cytotoxicity and IFN-␥ secretion within a single CD8 T cell. Consistent with the results described here, Ma et al (21) have described clearance of an IL-21-secreting tumor by a CD8-and NK cell-dependent mechanism requiring perforin but not IFN-␥. Furthermore, we have observed an E.G7 tumor-infiltrating, Ag-specific population of granzyme B high, IFN-␥ negative CD8 effector cells (J. M. Curtsinger, M. Y. Gerner, D. C. Lins, and M. F. Mescher, unpublished data).…”
Section: Discussionsupporting
confidence: 80%
“…60 Other NK cell activators, such as IL-12, IL-15, IL-18 and IL-21, have been successfully tested in preclinical cancer models as part of various vaccination strategies. 92,93 In the presence of IL-15 and hydrocortisone (HC), autologous NK cells can be activated and expanded in vitro, and these cells are effective in vivo in a lung metastasis mouse model which accumulated in lung tissue and were retained in the tumor-bearing site for more than 3 days. Extremely high IL-15 doses were necessary to observe any meaningful antitumor effects in vivo.…”
Section: Conception Of Nk Cellsmentioning
confidence: 99%
“…Considering the profound effects of IL-21 on T and NK cells and the proven antitumor effects of another gammachain cytokine (IL-2), it is not surprising that IL-21 has antitumor effects (Wang et al, 2003). These have been observed in animal models including melanoma, sarcoma, and bladder and renal cell carcinoma (Ma et al, 2003;Furukawa et al, 2006;Søndergaard et al, 2007). Through depletion studies, the antitumor activity of IL-21 was shown to depend on NK cells or CD8+ T cells, or both, depending on the tumor model.…”
Section: Discussionmentioning
confidence: 97%